Design and implementation of fast and highly precise water magnetizer - Mohammed A. Mohammed; Ahmed J. Abid (Universitas Ahmad Dahlan, 2020)
In the last decades, researchers have widely discussed the effects of magnetized water on many biological and industrial aspects; many studies have also examined the effects of magnetization on water physical and chemical properties and shown a slight increase in the water pH level for the drinking water after magnetizations. This article presents a new practical model to magnetize the tap drinking water with permanent, and adjustable magnets to ensure fast and precise results. A new smart system is designed and implemented to calculate the required magnetic flux density, and the exposuretime based on the difference in the measured pH level of the water atthe inletand outlet pipes.Three permanent magnets, with magnetic flux densities of 500, 1000, and 1500 Gauss (G), are installed at different pipe routes, with added to a variable magnet on the main water outlet. The results show a promising prototype that is not only processing the water efficiently but also supply much data about the water properties, which can be led to more findingsin this field.